2022
DOI: 10.3389/fpsyg.2022.730917
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Signing Avatars Vary Depending on Hearing Status, Age of Signed Language Acquisition, and Avatar Type

Abstract: The use of virtual humans (i.e., avatars) holds the potential for interactive, automated interaction in domains such as remote communication, customer service, or public announcements. For signed language users, signing avatars could potentially provide accessible content by sharing information in the signer's preferred or native language. As the development of signing avatars has gained traction in recent years, researchers have come up with many different methods of creating signing avatars. The resulting av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Another challenge in SL avatars is the need for the avatars to be realistic and natural-looking. A study on the attitudes of D/HH communities of SL avatars showed that the participants had a higher preference for the avatar that was more human-like than the others [4]. Their results showed that the adoption of SL avatars was not only dependent on the fluid motion of signing but also on the appearance of the SL avatar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge in SL avatars is the need for the avatars to be realistic and natural-looking. A study on the attitudes of D/HH communities of SL avatars showed that the participants had a higher preference for the avatar that was more human-like than the others [4]. Their results showed that the adoption of SL avatars was not only dependent on the fluid motion of signing but also on the appearance of the SL avatar.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of individuals working as SL interpreters is relatively low, leading to high service costs. Some D/HH individuals also opt out of utilizing available SL interpreters due to lack of privacy, which further impacts their access to information especially in cases of emergency [3,4].…”
Section: Introductionmentioning
confidence: 99%